2020
DOI: 10.1111/bcp.14355
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies in immune checkpoint inhibitor drug development: How far are we from the paradigm shift?

Abstract: The development of immune checkpoint inhibitors (ICI) represents a major milestone in immune‐oncology. Over the years these agents have demonstrated efficacy in an increasing array of malignancies. Despite this success however, significant challenges remain. Novel approaches to both drug development and trial design are required to incorporate the unique pharmacokinetic and pharmacodynamic properties of ICIs. Further, it has also been established that the benefit of ICIs is limited to only a subset of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 164 publications
0
17
0
Order By: Relevance
“…The introduction of immune-oncology therapies for the treatment of cancer marked a shift away from targeting cells to utilising the immune system to fight cancer. These therapies have become standard of care for many different tumour types [1] as they offer the possibility of long-term survival and improved toxicity profile for cancer patients when compared to chemotherapies. The first immune-oncology therapy approved by the Australian Therapeutics and Goods Administration (TGA) was ipilimumab for treatment of melanoma in 2012 (Table 1).…”
Section: Hansoo Kim Danny Liew and Stephen Goodallmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of immune-oncology therapies for the treatment of cancer marked a shift away from targeting cells to utilising the immune system to fight cancer. These therapies have become standard of care for many different tumour types [1] as they offer the possibility of long-term survival and improved toxicity profile for cancer patients when compared to chemotherapies. The first immune-oncology therapy approved by the Australian Therapeutics and Goods Administration (TGA) was ipilimumab for treatment of melanoma in 2012 (Table 1).…”
Section: Hansoo Kim Danny Liew and Stephen Goodallmentioning
confidence: 99%
“…Another area that has drawn a lot of attention recently are combination treatment with IO therapies. There are more than 180 phase trials examining IO therapies in combination with other IO therapies, chemotherapies, radiation therapy as well as biological therapies according to a recent review [1]. One of the first IO combination therapies to receive market authorisation was ipilimumab in combination with nivolumab for the treatment of advanced melanoma.…”
Section: Immuno-oncology Insights Price and Financial Costmentioning
confidence: 99%
“…Since the 21st century, immune checkpoint inhibitor (ICI) has gradually attracted the attention of tumor community ( Glisch et al, 2020 ; Singh et al, 2020 ; Watson et al, 2020 ; Luo et al, 2021 ). And studies have increasingly confirmed the effectiveness of these immunotherapies for malignant tumors ( Ferris et al, 2016 ; Burtness et al, 2019 ; Paz-Ares et al, 2019 ; Schmid et al, 2020 ; Colombo et al, 2021 ; Hua et al, 2021 ; Jiang et al, 2021 ; Paz-Ares et al, 2021 ; Zhou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms employed by the cancer cells for immune evasion and surveillance and its targeting by monoclonal antibodies has resulted in the development of highly powerful and effective therapies for the treatment of cancers. 16 Similarly, a better understanding of the mechanism(s) employed by the tumors to induce a phenotypic change in normal fibroblasts and vascular endothelial cells to partner with tumors, may provide very effective targets for interruption of tumor growth. Imaging agents like 68 Ga-FAPI can play an important role in this direction.…”
mentioning
confidence: 99%